Tariffs and Other Measures of Trade Control: A Survey of Recent Developments - Stern, Robert M. (Journal of Economic Literature, 1973)
I am indebted to E. J. Berg, A. V. Deardorff, J. D. Richardson, W. F. Stolper, members of the Research Seminar in International Economics at the University of Michigan, and anonymous referees for helpful comments on an earlier version of this paper. Financial assistance was pro. vided in part by National Science Foundation grant GS-3073 to support research in international economics at the University of Michigan.